Effect of Methylphenidate on Sleep Parameters in Children with ADHD - Lee, Sang Heon (Korean Neuropsychiatric Association, 2012)
OBJECTIVE: The primary aim of this study was to investigate the acute impact of methylphenidate (MPH) on sleep parameters in attention-deficit/hyperactivity disorder (ADHD) children. The second aim was to investigate the different effects of intermediate- and longacting MPH on sleep parameters. The third aim was to test the different effects of dose and age on sleep parameters. METHODS: Ninety-three ADHD children were enrolled and randomized to two different MPH preparations. Baseline and daily sleep diaries were evaluated for four weeks after taking medication. Weekday and weekend bedtimes, wake-up times, sleep latencies and total sleep times were compared by weeks. RESULTS: After taking MPH, there was a significant delay in bedtimes and a significant reduction of total sleep time (TST) both on weekdays and at weekends. There was also a significant delay in wake-up time on weekdays. However, the difference was applied to younger age group children only. There was no difference in changes of TST between metadate-CD and OROS-MPH. There also was no difference in changes of TST with different doses of MPH. CONCLUSION: MPH had negative impacts on sleep among young ADHD children, but different preparations and doses did not affect the result.